2023
DOI: 10.1021/acs.energyfuels.2c04116
|View full text |Cite
|
Sign up to set email alerts
|

Determining Nuclear Magnetic Resonance Surface Relaxivity of Shales

Abstract: Nuclear magnetic resonance, as an extensively recognized technique, is utilized to measure the pore size distribution of shales. However, the pore size distribution interpreted by nuclear magnetic resonance noticeably relies on the surface relaxivity (SR) of shales, which is influenced by many factors, including the measurement approach and mineralogical compositions. This paper chiefly deals with two approaches to measuring the surface relaxivity of shales based on a one-dimensional relaxation model. In conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Previous studies have reported a variety of methods for determining surface relaxivity. ,, For example, the surface relaxivity is determined based on the relationship between the inverse cumulative curve of mercury saturation obtained by MIP and the inverse cumulative curve of T 2 proportion. , However, the pore size of the macropore obtained by MIP is often nonlinear with respect to the T 2 value, , which may be due to the significant pore shielding effect as a result of the large difference between the macropore and the pore throat. Therefore, for some samples, it may be more appropriate to fit the surface relaxivity by the MIP data in the small pore range. , …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported a variety of methods for determining surface relaxivity. ,, For example, the surface relaxivity is determined based on the relationship between the inverse cumulative curve of mercury saturation obtained by MIP and the inverse cumulative curve of T 2 proportion. , However, the pore size of the macropore obtained by MIP is often nonlinear with respect to the T 2 value, , which may be due to the significant pore shielding effect as a result of the large difference between the macropore and the pore throat. Therefore, for some samples, it may be more appropriate to fit the surface relaxivity by the MIP data in the small pore range. , …”
Section: Methodsmentioning
confidence: 99%
“…At present, there are many methods used to characterize the pore microstructure of coalbed methane reservoirs, and there are three main types: The first is the non-material contact method, such as X-ray diffraction (XRD) [16] and nuclear magnetic resonance (NMR) [17], in which X-ray diffraction is used to determine the mineral structure of coal seams and the analysis of coal phase composition [16]. Although nuclear magnetic resonance technology can quickly and non-destructively determine the pore structure of coal and rock, its microscopic morphology cannot be intuitively observed [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of this method is that the relative magnitude of the surface relaxivity of the samples can be conveniently obtained by using basic physical parameters. Besides, the digital petrophysics method, experimental parameter method, and diffusion method have also been used to determine the surface relaxivity. …”
Section: Introductionmentioning
confidence: 99%